"The Causal Factors of The Student Ignorance in Speaking English" - Gustiana, Dinda; Al-zuhda, Najwa; Sholikhah, Siti; Fadilah, Qorri; Hidayat, Yulia; Santoso, Didik (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research is a sample of the application of qualitative method. This research builds its structure and is reported descriptively by using words although a numerical rubric of speaking is used to acquire the components of their speaking difficulties. The interview is done to obtain individual perspective on the speaking activity and is analyzed by using condensed meaning technique. The data of the research is taken from interview and speaking rubric. The interviews are done to acquire individual perspective of the speaking activities. The research is done by analyzing the data of interview. The results of the interview found from the causal factors of the students' ignorance in speaking English are: (i) students' mentality (embarrassed, nervous, afraid of making grammar mistakes, lack of self-confidence), and (ii) teachers who are boring in teaching.